Glycosylation and surface expression of the influenza virus neuraminidase requires the N-terminal hydrophobic region. - Markoff, L (1984)
A full-length double-stranded DNA copy of an influenza A virus N2 neuraminidase (NA) gene was cloned into the late region of pSV2330, a hybrid expression vector that includes pBR322 plasmid DNA sequences and the simian virus 40 early region and simian virus 40 late region promoters, splice sequences, and transcription termination sites. The protein encoded by the cloned wild-type NA gene was shown to be present in the cytoplasm of fixed cells and at the surface of "live" or unfixed cells by indirect immunofluorescence with N2 monoclonal antibodies. Immunoprecipitation and sodium dodecyl sulfate-polyacrylamide gel electrophoretic analysis of [35S]methionine-labeled proteins from wild-type vector-infected cells with heterospecific N2 antibody showed that the product of the cloned NA DNA comigrated with glycosylated NA from influenza virus-infected cells, remained associated with internal membranes of cells fractionated into membrane and cytoplasmic fractions, and could form an immunoprecipitable dimer. NA enzymatic activity was detectable after simian virus 40 lysis of vector-infected cells. These properties of the product of the cloned wild-type gene were compared with those of the polypeptides produced by three deletion mutant NA DNAs that were also cloned into the late region of the pSV2330 vector. These mutants lacked 7 (dlk), 21 (dlI), or all 23 amino acids (dlZ) of the amino (N)-terminal variable hydrophobic region that anchors the mature wild-type NA tetrameric structure in the infected cell or influenza viral membrane. Comparison of the phenotypes of these mutants showed that this region in the NA molecule also includes sequences that control translocation of the nascent polypeptide into membrane organelles for glycosylation.